An Investigation of Financial Investment Intention using Covariance-Based Structural Equation Modelling - Lim, Thien Sang; Rasid Mail; Mohd Rahimie Abd Karim; Zatul Karamah Abdul Baharul Ulum; Mazalan Mifli; Junainah Jaidi (2020)
Purpose: Decision-making process about financial investment is complicated. Relying on modern financial theory to explain behaviours of individual investors is inadequate because it focuses on the objective risk as the determinant for making investment decisions under the assumption that individuals are rational. The current study, which was built from the financial, sociological and psychological perspectives, investigated the predictors of risk perception and determined the association of risk perception and attitude toward financial investment intention. This study served the purpose of unravelling the complexity of the financial investment decision-making process among individuals. Design/methodology/approach: The research framework was based on Perception Formation Model (PFM) with further support from the Theory of Planned Behaviour, decision making models under risk, and knowledge-attitudebehaviour model. Purposive-sampling method was adopted. The dataset, which consisted a total of 492 responses from income earners below the age of prime savings years were entered for analysis. Twelve hypotheses were tested using the Analysis of Moment Structures (AMOS) statistical software. Findings: Measurement-model assessment revealed the data fitted well to the research model Results from the structural-model assessment revealed subjective knowledge, peer influence, internet influence, and risk propensity had a significant relationship with favourable risk perception. Consistent with the PFM proposition, it was found favourable risk perception significantly related to higher intention toward financial investment. Research limitations/implications: The resultant outcomes strengthen the understanding of how financial investment decision is performed by individuals, which is crucial in the personal-finance industry, especially in promoting a long-term and meaningful client-advisor relationship. Interestingly, objective knowledge, which measured the actual level of financial knowledge was found to be insignificantly associated with risk perception and intention toward financial investment. As a sizeable financial literature posited financial knowledge has impact on decision-making process, future study could perhaps examine whether objective knowledge could contextually alter the relationship between predictors and the endogenous variable. Originality/value: The study has successfully identified several predictors for risk perception about financial investment and provided an empirical link for knowledge-perception-attitude-intention, thus, enriching the behavioural finance literature. The research model was robust as it was formulated based on the three major pillars of behavioral finance, namely: financial, sociological, and psychological perspectives.